Student Interest In Investing In Sharia Capital Market: What Is The Influence Of Product Information? - Wahyuni, Elmiliyani; Gusnita, Helma (Al-bank: Journal of Islamic Banking and Finance, 2022)
The purpose of this study was to determine the effect of product information (capital market instruments) on interest in investing in the Islamic capital market. The variables in this study consisted of the marketing of capital market instruments and interest in investing in the Islamic capital market. This type of research is field research with quantitative methods. The steps of data analysis using analysis tools of validity test, reliability test, correlation analysis, and hypothesis testing (simple linear regression test, t-test, and analysis of determination). The result of this study is that information on capital market instruments has a positive and significant effect on interest in investing in the Islamic capital market. One of the implications of this research is that the Islamic Investment Gallery IAIN Batusangkar further enhances the dissemination of information on Islamic capital market products to students so that they are interested in investing